2022
DOI: 10.3390/foods11050629
|View full text |Cite
|
Sign up to set email alerts
|

Nano Filling Effect of Nonmeat Protein Emulsion on the Rheological Property of Myofibrillar Protein Gel

Abstract: Incorporation of vegetable oils through pre-emulsification has received notable attention for delivering polyunsaturated fatty acids to emulsified-type meat products. The two important influencing factors of the rheological property of composite myofibrillar protein (MP) gel are emulsion droplet size and active or inactive interaction between interface and meat proteins. Incorporation of nonmeat protein emulsion (2% protein (w/w), egg-white protein isolate (EPI), porcine plasma protein (PPP), or sodium caseina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…For example, sausages emulsified with microparticulate whey protein show no unfavorable impacts on the organoleptic properties of fat-reduced products (Ozturk-Kerimoglu et al, 2022). Cai et al (2022) also found that nanosized nonmeat protein emulsions displayed favorable filling effects on the MP gel matrix subjected to heating. However, the complex relationship between structural components and their quality-related attributes warrants a deeper investigation.…”
Section: Nonmeat Proteinsmentioning
confidence: 90%
See 2 more Smart Citations
“…For example, sausages emulsified with microparticulate whey protein show no unfavorable impacts on the organoleptic properties of fat-reduced products (Ozturk-Kerimoglu et al, 2022). Cai et al (2022) also found that nanosized nonmeat protein emulsions displayed favorable filling effects on the MP gel matrix subjected to heating. However, the complex relationship between structural components and their quality-related attributes warrants a deeper investigation.…”
Section: Nonmeat Proteinsmentioning
confidence: 90%
“…Cai et al. (2022) also found that nanosized nonmeat protein emulsions displayed favorable filling effects on the MP gel matrix subjected to heating. However, the complex relationship between structural components and their quality‐related attributes warrants a deeper investigation.…”
Section: Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…MP was extracted according to our previously described method [17]. All extraction steps were strictly operated in a cold storage facility at 0-4 • C. For subsequent testing, the final MP concentration was determined by the biuret method, and bovine serum albumin (BSA) was used as the standard.…”
Section: Preparation Of Mpmentioning
confidence: 99%
“…The viscosity of emulsions within 24 h was conducted following our previously reported method [17]. The behavior of emulsions can be fitted using the Ostwald-de Waele model, and the model has been reported for meat-production applications [24].…”
Section: Viscositymentioning
confidence: 99%